Platelet-Associated Anti-Glycoprotein (GP) IIb-IIIa Autoantibodies in Chronic Immune Thrombocytopenic Purpura Mainly Recognize Cation-Dependent Conformations: Comparison with the Epitopes of Serum Autoantibodies - Kosugi, Satoru; Tomiyama, Yoshiaki; Shiraga, Masamichi; Kashiwagi, Hirokazu; Mizutani, Hajime; Kanakura, Yuzuru; Kurata, Yoshlyuki; Matsuzawa, Yuji (Thrombosis and Haemostasis, 1996)
Platelet-associated and serum anti-glycoprotein (GP) IIb-IIIa autoantibodies were investigated in 57 patients with chronic immune thrombocytopenic purpura (ITP). In modified antigen capture ELISA (MACE) using GPIIb-IIIa-specific-, GPIIb-specific-, and GPIIIa-speci-fic-monoclonal antibody (mAb) for antigen capture, platelet-associated anti-GPIIb-IIIa antibodies were detected in 14 out of 37 patients (38%), and these antibodies could be detected with all 3 mAbs used for antigen capture. In the MACE using EDTA-treated platelets at 37° C, the reactivity of platelet-associated anti-GPIIb-IIIa antibodies in 9 out of 10 patients was markedly reduced in both cases of GPIIb-specific- and GPIIIa-specific-mAb used. Immunoprecipitation experiments further confirmed that the EDTA-treatment abrogated the antigenicity of GPIIb-IIIa for platelet-associated antibodies in 2 patients. Serum anti-GPIIb-IIIa autoantibodies were detected in 23 out of 57 patients (40%). However, only 7 out of 23 serum anti-GPIIb-IIIa antibodies could be detected with all 3 mAbs. The MACE using EDTA-treated platelets further showed that the features of serum anti-GPIIb-IIIa antibodies were different from those of platelet-associated antibodies even in the same patient. Our data demonstrate that the platelet-associated anti-GPIIb-IIIa antibodies mainly recognize the cation-dependent antigenic determinants on GPIIb-IIIa and that serum anti-GPIIb-IIIa antibodies may contain some components which differ in specificity from platelet-associated antibodies.